Chapter 1 Unintended Consequences of EU External Action - Burlyuk, Olga (Taylor & Francis, 2019)
"There is a gap in IR and EU scholarship concerning unintended consequences in an international context, leaving this important phenomenon understudied. To fill this gap, a conceptualisation of unintended consequences is offered, and a set of common research questions are presented, highlighting the nature (what), the causes (why) and the modes of management (how) of unintended consequences of EU external action. The Special Issue contributes to the study of the EU as an international actor by broadening the notion of the EU's impact abroad to include the unintended consequences of EU (in)actions and by shedding new light on the conceptual paradigms that explain EU external action."